PENGARUH FAMILY OWNERSHIP, PERUBAHAN TARIF PAJAK DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN - Elfina Astrella Sambuaga (Universitas Bunda Mulia, 2017)
This study aims to provide empirical evidence related to the influence of family ownership, tax reform on corporate debt policy, and further prove the impact on the firm value.This study examined the effect of changes in tax rates in 2009 and 2010 on the relationship between family ownership structure and corporate debt policy. The population of this research is manufacturing companies listed in Indonesia Stock Exchange for 8 consecutive years (2006-2013), with the period of observation for 7 years (2007-2013). A period of 8 years was taken to see a company that is consistently listed on the Stock Exchange prior to the end of the observation period. The result of this study shows that tax reform from progressive tax rates to a flat rate does not affect the relationship between family ownership structure and corporate debt policy. In contrast to the year 2009, changing rate from 28% to 25% in late 2010 was a significant effect on the debt policy with the company of family ownership. Based on the results, it was found that family ownership and debt policy significantly affect the company's enterprise value. It can be concluded, the higher the family ownership, the company's value would be diminished. Instead, the company's value will increase when the company adds to its debt policy.Keywords : debt policy, family ownership, firm value, tax reform.